The Challenges and Successes of Non-Governmental Organizations in Palestinian Refugee Camps in Lebanon from 1967 to 1982; The Case of the American Near East Refugee Aid (ANERA) - Minkova, Nicole (Université d'Ottawa / University of Ottawa, 2019)
This thesis studies a by-product of the continuing and complex Arab-Israeli conflict: the Palestinian refugee diaspora in Lebanon, and the efforts of Western charitable organizations with this population. The rise of the non-governmental organization (NGO) movement embroiled the Western world in the Middle East as a new form of intervention, with the aim of providing emergency relief in the short term and plans for development in the long term. This research studies how Palestinians came to live in their host countries with the help of NGOs, and to determine what the challenges and successes of these organizations were. For this study, the American Near East Refugee Aid (ANERA) organization is used as a case study by looking at its history of interaction with Palestinians between the War of 1967 and the Israeli invasion of Lebanon in 1982, a decade and a half marked by war and exodus. Using ANERA’s annual reports, newsletters, board meeting reports, and interviews with individual Palestinians who were raised in Lebanon, the research looks at the history and ethical complications of the international NGO movement. Furthermore, this thesis analyses the logistical challenges and achievements of ANERA in their programming in Lebanon and the way that Palestinians were portrayed by ANERA back to their American public. Finally, the Palestinian perspective is taken into account to understand the impact of Western NGOs on their own community. Ultimately, this study seeks to determine how what has been ANERA’s historical experience with Palestinian refugees in Lebanon.
Keywords: palestine; refugees; lebanon; non-governmental organization